Caracterização química e potencial energético da biomassa derivada da casca de coco verde - Martins, Luís Henrique Pereira (Universidade Federal de São Carlos, 2025)
Since the end of the 20th century, growing concerns about rising greenhouse gas emissions and the resulting global warming have driven the search for renewable energy sources, such as solar, wind and biomass, the latter mainly involving the burning of organic matter from wood waste. In this context, biomass derived from coconut husk bagasse, although less explored compared to other sources, such as sugarcane bagasse, eucalyptus firewood and agricultural waste, has emerged as an alternative for the production of renewable energy. In addition to its energy potential, the use of coconut husk bagasse can contribute to promoting environmental sustainability, particularly in urban areas where excessive disposal of coconut waste becomes a problem. Locations such as kiosks and coconut processing facilities are often responsible for high volumes of waste that could be used to reduce the accumulation of garbage and, at the same time, provide a source of renewable energy. Investigating green coconut bagasse is essential to understanding its chemical composition and its potential as a biomass. Thus, the objective of this work is to study the chemical composition of green coconut bagasse based on the procedures of specific standards of ABNT NBR. This analysis allows the evaluation of the presence of water (moisture), cellulose and lignin, in addition to potentially significant levels of carbon and nitrogen, essential elements for determining the energy potential of the material. Based on these results, the possibilities of using green coconut bagasse as a sustainable source of energy in industrial and/or commercial applications will be explored, aiming to advance discussions on the diversification of the Brazilian energy matrix and possible strategies for mitigating the environmental impacts associated with conventional energy sources.
Chemical characterization and energy potential of biomass derived from green coconut husk
Keywords: Biomassa; Casca de coco; Energia renovável; Caracterização química; Poder calorifico; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA